Intratumor Heterogeneity of Perfusion and Diffusion in Clear Cell Renal Cell Carcinoma: Correlation with Tumor Cellularity - Yuan, Qing (Clin Genitourin Cancer, 2016)
BACKGROUND: Magnetic Resonance Imaging (MRI) has the potential to non-invasively inform about tumor micro-environment. A correlation between arterial spin labelled (ASL) MRI and tumor vasculature has been previously demonstrated, however, its correlation with tumor cellularity is unknown. PURPOSE: To assess intratumor heterogeneity of perfusion and diffusion in vivo in clear cell renal cell carcinoma (ccRCC) using MRI, and correlate these findings with tumor vascularity and cellularity at histopathology. PATIENTS AND METHODS: 23 ccRCC patients underwent ASL and diffusion-weighted MRI prior to surgery after signing an informed consent in this prospective IRB-approved, HIPAA-compliant study. Quantitative ASL perfusion and diffusion were measured in two areas within the same tumor with high and low perfusion. Microvessel density (MVD) on CD31 and CD34 immunostains and tumor cellularity in anatomically co-registered tissue samples were correlated to MRI measurements (Spearman; P<0.05 statistically significant). RESULTS: ASL perfusion (p<0.0001), CD31 MVD (p=0.02), CD34 MVD (p=0.04) and cellularity (p=0.002) from high and low perfusion areas were significantly different across all tumors. There were positive correlations between (1) tumor cellularity and CD31 MVD (ρ=0.350,P=0.021); (2) CD31 and CD34 MVD (ρ=0.838,P<0.0001); (3) ASL perfusion and cellularity (ρ=0.406,P=0.011); (4) ASL perfusion and CD31 MVD (ρ=0.468,P=0.003); and a negative correlation between tissue diffusion coefficient and cellularity (ρ=−0.316,P=0.039). CONCLUSION: Tumor areas with high ASL perfusion exhibit higher cellularity and MVD compared to areas with low perfusion in the same tumor. A positive correlation between tumor vascularity and cellularity in ccRCC is newly reported. A negative correlation between tumor diffusion and cellularity is confirmed.